Hubungan Antara Intensitas Membaca Manga Genre Boys Love Terhadap Sikap Positif Kepada Homoseksual - Ratna Indra Setyaningurm; Wanodya Kusumastuti; Widyaning Hapasari (Asosiasi Ilmuwan Pendidikan, Sosial, dan Humaniora Indonesia, 2025)
Manga, or Japanese comics, are becoming increasingly popular among Indonesian boys and can be easily found online. Fujoshi refers to female fans and fundashi refers to male fans of the “boys love” genre, which is characterized by romantic comedies involving male protagonists in media such as literature, anime, and video games. The intensity of reading a particular “boys love manga” genre and a favorable view of homosexuality are the focus of this study. A correlation coefficient of 0.227 was obtained, indicating a weak but positive relationship of 22.7%, between the two variables in this study using a quantitative correlational method. A total of 351 participants in this study were tested for their hypotheses using the Pearson Product Moment correlation. Individual attitudes can be shaped by many factors, including their own life experiences, the opinions of influential people in their lives, cultural norms, the media, the education system, religious organizations, and even their own emotions. All those who took part in this study found a positive interpretation of homosexuality that brought tolerance.